EFFECTIVE WAYS OF ORGANIZING METHODOLOGICAL SERVICE IN SCHOOL EDUCATIONAL ORGANIZATIONS (American Journal of Research in Humanities and Social Sciences, 2023)
In the article in the organization of preschool education organization of methodical service and important duties of a methodist are discussed. Information about the task, main directions and principles of methodical service is also provided. Recommendations on the effective use of various approaches, forms and tools in the organization of methodical service are given.